Providers' perceptions of implementing standardized postpartum family planning: a qualitative study of midwives and nurses in GhanaAJOG Global Reports at a Glance - Sarita Sonalkar; Ernest Maya; Chris Guure; Arden McAllister; Dzifa Adimle Puplampu; Roseline Dansowaa Doe; Mary Eluned Gaffield; James Kiarie (AJOG Global Reports)
Background: The World Health Organization publishes and maintains evidence-based guidance for the delivery of essential family planning services in the postpartum period. Despite significant time and effort in the development of these guidelines in the past decades, a significant unmet need for postpartum family planning persists, exposing an implementation gap. Implementation strategies involving education and infrastructure support can improve family planning uptake and mobile health interventions are a feasible adjunct in improvement of health outcomes. Objective: We sought to understand provider perceptions of feasibility, acceptability, and appropriateness of implementation of the Postpartum Family Planning Package, which involved provider use of the World Health Organization Medical Eligibility for Contraceptive Use Mobile Application with a one-on-one counseling strategy. Study Design: We implemented the Postpartum Family Planning Package at three hospitals in Greater Accra and Eastern Regions, Ghana. We conducted in-depth interviews with 23 providers who used the Postpartum Family Planning Package for at least three months. Study design, data collection, analysis, and interpretation were guided by the Consolidated Framework for Implementation Research. We interpreted data using thematic analysis. Results: Providers indicated that use of one-on-one counseling and the mobile application in hospital-based postpartum care delivery was acceptable, feasible, and appropriate. Respondents described the resultant increased perceived trust between patients and providers as well as more effective and efficient information exchange. Endorsement for the use of the World Health Organization Medical Eligibility for Contraceptive Use Mobile Application by the facility leadership motivated providers to use it. The primary barrier to incorporation of one-on-one counseling was lack of privacy on the postnatal wards. Conclusion: Providers perceived the implementation of the Postpartum Family Planning Package as feasible, acceptable, and appropriate. Creation of private spaces on the postnatal ward for counseling and continued buy-in by the facility leadership would likely enhance the impact of the strategy. Given the widespread use of mobile technology and the continued unmet need for postpartum contraception, we recommend evaluating this strategy in a broad range of settings internationally, including in lower-resource settings.